An approach to the analysis of observability and controllability in nonlinear systems via linear methods - Zhirabok, Alexey; Shumsky, Alexey (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to the problem of observability and controllability analysis in nonlinear dynamic systems. Both continuous- and discrete-time systems described by nonlinear differential or difference equations, respectively, are onsidered. A new approach is developed to solve this problem whose features include (i) consideration of systems with non-differentiable nonlinearities and (ii) the use of relatively simple linear methods which may be supported by existing programming systems, e.g.,Matlab
Keywords: nonlinear dynamic systems; observability; controllability; linear systems; decomposition